Inclure les « n’ayants pas droit » : Terres collectives et inégalités de genre au Maroc - Yasmine Berriane (L’Année du Maghreb)
The recent emergence in Morocco’s public debate of collective lands and their increased commodification is partly due to the protest actions that are led against the ways this commercialisation is taking place. The actions carried out by women have become the most visible ones today. Since 2007, they have been protesting against their exclusion from the right to use collective lands. This right was eventually given to them via a series of ministerial circulars that were issued by the ministry between 2009 and 2012. The article focuses on the legal and normative references used, at different scales, to legitimize the inclusion of women amongst the lists of those entitled to benefit from collective land. After a presentation of the gendered character of the regime regulating collective land, the article analyses how the ministry of the Interior justifies the obligatory inclusion of women within the lists of beneficiaries. Through the case of the Mehdawa community, it finally illustrates how the delegates of this community are legitimizing the implementation of the new ministerial directives at the local level by re-adapting the arguments put forward by the State.